MIDDLE ARTINSKIAN (EARLY PERMIAN) ECOLOGICAL EVENT: A CASE STUDY OF THE URALS AND NORTHERN TIMAN - Kossovaya O.L.; Guseva E.A.; Lukin A.E.; Zhuravlev A.V. (My University, 2001)
Biotic and abiotic changes established in the middle Artinskian of several sections of the northern Timan and the western slope of the Central Urals are discussed. Data on the distribution of corals, composition of the biota as a whole, palaeotemperature and microfacies changes are presented for the first time. The determination of the stratigraphic levels is based on the new and revised biostratigraphic data. The palaeotemperature decline coincides with the maximal flooding surface and is considered as a possible cause of the ecological event triggering the turnover or extinction of many faunal groups. The event level was recognized in the coeval deposits along the Pangea shelves.
Keywords: Permian; Rugosa; Cyathaxonia fauna’; Moscovian; Artinskian-Ufimian; ecological differentiation; palaeogeography; Палеозой::Каменноугольная::Средний::Московский; Paleozoic::Permian; Paleozoic::Carboniferous::Pennsylvanian::Middle::Moscovian; Палеозой::Пермская